Coverage and factors associated with non-vaccination against hepatitis B in newborns in Peru - Correa-Leiva , Pauleth (2025)
Objective: To determine the coverage and factors associated with non-vaccination against hepatitis B in newborns in Peru. Materials and methods: Multiple cross-sectional, the population consisted of children under five years of age. The source of information was a combination of vaccination cards and mother's report.  Results: In the 2023 demographic survey, the vaccination rate was 91.9%. The characteristics associated with non-vaccination in the generalized linear models (p value ˂ 0.05) were: i) home births and births in private clinics, ii) cesarean births, iii) not having received the BCG vaccine, and iv) not belonging to the mountain region. Conclusion: The percentage of children vaccinated in the 2023 demographic survey exceeded 90.0%. The factors that were shown to be associated with non-vaccination were place of delivery (home, private clinic), cesarean delivery, not having received the BCG vaccine, and not belonging to the mountain region.